Dynamic Analysis and Optimization of a Bionic Flapping-Wing Aircraft - JIN, Xiaoyi; ZHOU, Xiaolei; TIAN, Peipei; ZHANG, Liqiang; NIE, Zhengwei (Engineering Transactions, 2016)
This research has been conducted for the purpose of developing bionic flapping-wing aircraft. In this paper, wings are regarded as flexible, and the response issues of wings under certain excitation functions are investigated. The research is based on preliminary studies about bionic flapping wings and aims to provide data references to aid the selection of electrical actuators and the design of driving mechanisms for bionic flapping-wing aircraft at a later stage. The dynamic analysis shows that the response functions adapt well to the flapping movements of the wings. However, there are mutational situations in the wing structure transformation which are bad for structural stability, and cause there to be too little lift force.Under such circumstances, the minimum norm of low-order vibration mode difference values is used as the optimization principle to conduct the structural optimization. The optimization results and the wing flutter test both show that the optimized wings can better avoid structural mutations and their response functions can also better meet the design requirements.